1982
DOI: 10.1002/1097-0142(19820415)49:8<1734::aid-cncr2820490833>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

The risk of spontaneous pneumothorax in patients with osteogenic sarcoma and testicular cancer

Abstract: Seven cases of unilateral, spontaneous pneumothorax were found in a retrospective study of 63 patients with osteogenic sarcoma who were admitted to The Norwegian Radium Hospital (NRH) in the period 1970--1977. The relative risk of pneumothorax developing doubled, from 7--14%, after the introduction of chemotherapy for this disease at NRH. This difference was not statistically significant. Pneumothorax developed in two of 18 patients (11%) with lung metastases who never received chemotherapy. Pneumothorax occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 11 publications
1
23
0
Order By: Relevance
“…It has been hypothesized that the pneumothorax was the result of ruptures of the necrotic subpleural micro metastasis in patients treated with chemotherapy (2). However, Smevik and Klepp reported that the bullous change caused the metastatic pulmonary disease, and that the peripheral tumor produced partial bronchial obstruction and caused a ball-valve phenomenon (8). This case provided us with radiographic evidence of this phenomenon.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…It has been hypothesized that the pneumothorax was the result of ruptures of the necrotic subpleural micro metastasis in patients treated with chemotherapy (2). However, Smevik and Klepp reported that the bullous change caused the metastatic pulmonary disease, and that the peripheral tumor produced partial bronchial obstruction and caused a ball-valve phenomenon (8). This case provided us with radiographic evidence of this phenomenon.…”
Section: Discussionmentioning
confidence: 62%
“…The association of spontaneous pneumothorax with osteosarcoma is well known (1,6,7). Patients with osteosarcoma that have pulmonary metastases have a higher risk of spontaneous pneumothorax than patients with pulmonary metastatic carcinoma, but the reason for this remains unclear (8). It is also unclear whether there is any correlation between pneumothorax and lung metastasis (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5) Only one patient exhibited internal necrosis, with SSP occurring 31 days after chemotherapy initiation. We presume that SSP occurred because of internal ischemic changes for the large 95-mm lesion rather than because of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with metastatic osteosarcoma in the lung have a higher risk of spontaneous pneumothorax than patients with metastatic carcinoma, but the reason for this remains unclear [4]. Whether or not patients with osteosarcoma have pulmonary metastases, those who receive chemotherapy have a higher risk of spontaneous pneumothorax than those who do not [4]. It has been hypothesized that the pneumothorax was the result of ruptures of the necrotic subpleural micrometastasis in patients treated with chemotherapy [1].…”
Section: Discussionmentioning
confidence: 99%